Daytime Equatorial Spread F‐Like Irregularities Detected by HF Doppler Receiver and Digisonde - B. Olugbon; E. O. Oyeyemi; A. Kascheyev; A. B. Rabiu; A. A. Obafaye; O. O. Odeyemi; A. O. Adewale (Space Weather)
Abstract Daytime equatorial spread F (ESF) is not as common as nighttime ESF due to the presence of a highly conducting E‐layer during the daytime which counteracts the development of F‐layer plasma irregularities. This study presents two rare daytime ESF‐like events which occurred over an interval ∼2 h and were detected by the HF Doppler receiver located in Lagos (LAG: geographic: 3.27°E, 6.48°N; dip latitude −1.72°) and the Lowell Digisonde at Ilorin (ILR; 4.68°E, 8.50°N; dip latitude −1.25°), managed by Lowell GIRO Data Center (LGDC). Analysis of the first event revealed ∼30 min periodic oscillations in iso‐heights of ionospheric electron density. Shorter period (∼15 min) oscillations appeared simultaneously in HF Doppler measurements and these oscillations lasted nearly 3 h. Close inspection of the ionograms from ILR during this interval (1500–1800 UT) showed the occurrence of small‐scale spreading in the F‐layer trace which varied in altitude as the disturbance progressed. Computation of the linear growth rate of the collisional Rayleigh‐Taylor instability showed that the plasma instability was seeded by a traveling ionospheric disturbance (TID). The characteristics of the second event suggest that horizontal stratifications in plasma density distribution at the reflecting ionospheric layer were responsible for the spread F traces in the ionograms. Analysis of GPS TEC data from Nigeria during these events revealed the presence of wave structures consistent with TIDs.